Mu opioid receptors on vGluT2‐expressing glutamatergic neurons modulate opioid reward. (20th July 2020) - Reeves, Kaitlin C.; Kube, Megan J.; Grecco, Gregory G.; Fritz, Brandon M.; Muñoz, Braulio; Yin, Fuqin; Gao, Yong; Haggerty, David L.; Hoffman, Hunter J.; Atwood, Brady K.
Abstract: The role of Mu opioid receptor (MOR)‐mediated regulation of GABA transmission in opioid reward is well established. Much less is known about MOR‐mediated regulation of glutamate transmission in the brain and how this relates to drug reward. We previously found that MORs inhibit glutamate transmission at synapses that express the Type 2 vesicular glutamate transporter (vGluT2). We created a transgenic mouse that lacks MORs in vGluT2‐expressing neurons (MORflox‐vGluT2cre) to demonstrate that MORs on the vGluT2 neurons themselves mediate this synaptic inhibition. We then explored the role of MORs in vGluT2‐expressing neurons in opioid‐related behaviors. In tests of conditioned place preference, MORflox‐vGluT2cre mice did not acquire place preference for a low dose of the opioid, oxycodone, but displayed conditioned place aversion at a higher dose, whereas control mice displayed preference for both doses. In an oral consumption assessment, these mice consumed less oxycodone and had reduced preference for oxycodone compared with controls. MORflox‐vGluT2cre mice also failed to show oxycodone‐induced locomotor stimulation. These mice displayed baseline withdrawal‐like responses following the development of oxycodone dependence that were not seen in littermate controls. In addition, withdrawal‐like responses in these mice did not increase following treatment with the opioid antagonist, naloxone. However, other MOR‐mediated behaviors were unaffected, including oxycodone‐induced analgesia. These data reveal that MOR‐mediated regulation of glutamate transmission is a critical component of opioid reward. Abstract : In this study, the authors created a transgenic mouse line that lacked expression of Mu opioid receptors only in a subtype of glutamate neurons that express the Type 2 vesicular glutamate transporter. These mice had disrupted behaviors related to opioid reward but not ethanol or natural reward and had intact opioid analgesic responses. These findings indicate that Mu opioid receptors in glutamate neurons are major contributors to opioid reward related behaviors.